Polypharmacy as a Risk Factor for Clinically Relevant Sarcopenia: Results From the Berlin Aging Study II. (6th May 2017) - König, Maximilian; Spira, Dominik; Demuth, Ilja; Steinhagen-Thiessen, Elisabeth; Norman, Kristina
Abstract: Background: Sarcopenia affects more than 10% of older adults. Next to age-associated physiologic changes, diseases like diabetes or inflammatory, neurological, malignant and endocrine disorders may contribute to the development of sarcopenia. Likewise, polypharmacy, i.e., multiple drug use, is common among older adults. Although the two conditions frequently co-occur, the association of polypharmacy with sarcopenia has not yet been examined. We investigated the association of polypharmacy and sarcopenia in a large cohort of community-dwelling older adults (60–84 years). Methods: Thousand five hundred and two participants from the Berlin Aging Study II were included. Polypharmacy was defined as concurrent use of 5 or more drugs (prescription and nonprescription). Body composition was assessed with dual-energy X-ray absorptiometry, and appendicular lean mass (ALM) was calculated as sum of the four limbs' lean mass. Sarcopenia was defined as low ALM-to-body mass index (BMI)-ratio using validated sex-specific cutoffs. Results: Mean age was 68.7 ± 3.7 years, 50.7% were female. The median (interquartile range) number of drugs was 2 (1–4); 21.1% of subjects reported regular use of ≥5 drugs. Subjects with polypharmacy were more often sarcopenic according to the applied ALM/BMI-cutoffs (16.3% vs 6.9%, p < 0.001), with a higher BMI ( p < 0.001) and lower ALM/BMI ( p < 0.001), but no significant difference in mean ALM. Notably, polypharmacy was also associated with higher rates of reduced gait speed and exhaustion. Even after multivariable adjustment (sex, age, comorbid conditions and physical activity) polypharmacy was consistently associated with a significantly increased likelihood of sarcopenia (odds ratio = 2.24, 95% confidence interval [CI] = 1.33–3.75). Conclusion: Polypharmacy is associated with clinically relevant sarcopenia, as assessed by a low ALM/BMI.